2018
DOI: 10.1016/j.clcc.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Mucinous Differentiation in Metastatic Colorectal Carcinoma Can Be Explained by Distinct Molecular and Clinicopathologic Characteristics

Abstract: Compared with nonmucinous adenocarcinoma, the mucinous histologic type is associated with a worse prognosis, even when controlling for known prognostic features. This unique biologic behavior should be considered in the treatment and prognostic assessment of patients with CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…GNAS mutation has been previously described in mucinous neoplasms of the pancreas and peritoneal carcinomatosis from appendiceal adenocarcinomas 35,36 . While the clinical significance of GNAS mutation in primary CRC is vaguely understood, a recent review by Khan et al, 37 demonstrated that GNAS mutation was more common in mucinous CRC adenocarcinoma. In that series, GNAS mutation was present in 6.9% of mucinous adenocarcinomas and was a poor prognostic factor on univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…GNAS mutation has been previously described in mucinous neoplasms of the pancreas and peritoneal carcinomatosis from appendiceal adenocarcinomas 35,36 . While the clinical significance of GNAS mutation in primary CRC is vaguely understood, a recent review by Khan et al, 37 demonstrated that GNAS mutation was more common in mucinous CRC adenocarcinoma. In that series, GNAS mutation was present in 6.9% of mucinous adenocarcinomas and was a poor prognostic factor on univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous colon/appendix cancers display phenotypic and genotypic characteristics that are predictive of responses to dual MEK‐PI3K inhibition. Mucinous colon cancers are more likely to occur in younger female patients; particularly the right colon; follow the serrated pathway for carcinogenesis; and are more likely to have RAS, RAF, and GNAS mutations . Similarly, mucinous appendix cancers are almost always KRAS mutant, and low‐grade histology almost uniformly demonstrates GNAS mutations .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 90 SMAD4 -mutated ACAs reported poorer survival rates in patients with SMAD4 -mutated tumors, but did not include mucinous morphology as a potential risk factor [3]. Similarly, Mizuno et al reported worse survival, but did not report tumor morphology of the SMAD4 -mutated cancers [6], while Khan et al reported association of mucinous morphology with SMAD4 mutation and worse prognosis [11]. Recognizing these knowledge gaps, our comprehensive study using a stringent retrospective case-control design confirms that SMAD4 mutations are associated with higher tumor stage, nodal metastasis, tumor deposits in adipose tissue, mucinous morphology, and RAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also investigated the relationship between SMAD4 and other gene mutations, especially RAS genes since these two are closely associated. KRAS mutations have been reported to correlate with mucinous differentiation in CRCs [11,18], yet the mucinous differentiation in SMAD4 m tumors is independent of KRAS mutation status. Tumors with RAS mutations are known to be intrinsically resistant to anti-EGFR therapy [19,20]; however, it has been shown that SMAD4 mutation is an independent factor of resistance to anti-EGFR therapy [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation